ANALISIS PERGESERAN SHIFTING PARADIGM PENAFSIRAN: STUDI KOMPARATIF TAFSIR ERA KLASIK DAN KONTEMPORER - Dozan, Wely (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Da'wah of IAIN Langsa, 2020)
This paper aims to explore the paradigm shift in the interpretation of the Qur'an in the classical and contemporary eras in the path of interpretation of Ibn Kathir and Fazlur Rahman. The focus in this study examines the causes of shifts in interpretation and contextualization of the interpretation model. The type of research is library research so that in this study using qualitative (descriptive-analytical) research, it is research that describes the object to be critically examined, and looks for the roots of the character's thoughts. The approach that I want to use in this study is historical-analytical, that is, according to historical roots analytically the shift in interpretation occurs. The results of this study indicate that, the interpretation of interpretation in the classical and contemporary era of interpretation is caused by the shifting paradigm, namely the birth of a new methodological concept to prove the suitability between text and social relaity. The argumentation of Ibn Katsir's interpretation of the